Validation of the IMPROVE‐DD risk assessment model for venous thromboembolism among hospitalized patients with COVID‐19. Issue 2 (24th February 2021) - Spyropoulos, Alex C.; Cohen, Stuart L.; Gianos, Eugenia; Kohn, Nina; Giannis, Dimitrios; Chatterjee, Saurav; Goldin, Mark; Lesser, Marty; Coppa, Kevin; Hirsch, Jamie S.; McGinn, Thomas; Barish, Matthew A.; et al.
Abstract: Background: Antithrombotic guidance statements for hospitalized patients with coronavirus disease 2019 (COVID‐19) suggest a universal thromboprophylactic strategy with potential to escalate doses in high‐risk patients. To date, no clear approach exists to discriminate patients at high risk for venous thromboembolism (VTE). Objectives: The objective of this study is to externally validate the IMPROVE‐DD risk assessment model (RAM) for VTE in a large cohort of hospitalized patients with COVID‐19 within a multihospital health system. Methods: This retrospective cohort study evaluated the IMPROVE‐DD RAM on adult inpatients with COVID‐19 hospitalized between March 1, 2020, and April 27, 2020. Diagnosis of VTE was defined by new acute deep venous thrombosis or pulmonary embolism by Radiology Department imaging or point‐of‐care ultrasound. The receiver operating characteristic (ROC) curve was plotted and area under the curve (AUC) calculated. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using standard methods. Results: A total of 9407 patients were included, with a VTE prevalence of 2.9%. The VTE rate was 0.4% for IMPROVE‐DD score 0‐1 (low risk), 1.3% for score 2‐3 (moderate risk), and 5.3% for score ≥ 4 (high risk). Approximately 45% of the total population scored high VTE risk, while 21% scored low VTE risk. IMPROVE‐DD discrimination of low versus medium/high risk showed sensitivity of 0.971, specificity of 0.218, PPV of 0.036, and NPV of 0.996. ROC AUC was 0.702. Conclusions: The IMPROVE‐DD VTE RAM demonstrated very good discrimination to identify hospitalized patients with COVID‐19 as low, moderate, and high VTE risk in this large external validation study with potential to individualize thromboprophylactic strategies.